Silver-silicon dioxide spherical powder and preparation method and application thereof
The preparation of silver-silica spherical powder by ultrasonic micropore jet atomization method was solved, and the problems of sintering shrinkage mismatch and decreased conductivity during the sintering process were obtained. Silver-silica spherical powder with high spherical shape, smooth surface and adjustable conductivity were obtained, which met the application requirements of conductive silver paste for LTCC.
Patent Information
- Application Number
- CN202211258551.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-14
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-10-14
AI Technical Summary
The existing conductive silver paste is prone to sintering shrinkage mismatch during the sintering process, and the introduction of silica powder will lead to a decrease in the conductivity of the silver electrode and an increase in the viscosity of the paste, making it difficult to obtain a conductive silver paste with a high solids content.
Silver-silica spherical powder was prepared by ultrasonic micropore jet atomization method. Through the cooperation of the micropore metal film and annular piezoelectric ceramic sheet, a narrow particle size distribution was formed. After natural settlement and heat treatment, silver-silica spherical powder with high spherical shape, smooth surface, and adjustable conductivity was obtained.
It realizes high-quality preparation of silver-silica spherical powder, meets the application requirements of conductive silver paste for LTCC, is suitable for large-scale applications, and has low equipment requirements and low production costs.
Smart Images

Figure CN115673336B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of silver powder for conductive silver paste, and in particular to a silver-silicon dioxide spherical powder and a preparation method and application thereof. Background Art
[0002] With the rapid development of electronic information technology, electronic devices are increasingly demanding miniaturization, integration, modularization, high performance, and high reliability from their components. Low-temperature co-fired ceramic (LTCC), with its excellent electronic, mechanical, and thermal properties, has become the preferred material for achieving integration and modularization of electronic components, and is widely used in substrates, packaging, and microwave devices.
[0003] During the sintering process of low-temperature co-fired ceramics, both the ceramic material and the metal electrode shrink. If the ceramic substrate and the electrode slurry are not well matched, and their sintering mechanisms are different, sintering shrinkage mismatch can easily occur. Therefore, in order to reduce sintering shrinkage mismatch, it is necessary to improve the electrode slurry to improve the matching between the ceramic substrate and the electrode slurry.
[0004] Conductive silver paste is a commonly used electrode paste. Adding silica powder to the conductive silver paste can increase the onset temperature of the silver electrode's sintering shrinkage, adjust the final sintering shrinkage rate, reduce the sintering shrinkage mismatch between the silver electrode and the ceramic substrate, and reduce silver migration. However, silica powder has a high resistivity, and the introduction of too much silica powder will lead to a decrease in the conductivity of the silver electrode. Furthermore, if the introduced silica powder has poor fluidity, it may also lead to an increase in the viscosity of the paste and a decrease in the rheological properties, which is not conducive to screen printing of the paste and makes it difficult to obtain a conductive silver paste with a high solid content.
[0005] Spherical powder usually has good fluidity and is easy to obtain a high powder tap density, so adding spherical powder is one of the important measures to ensure that a conductive silver paste with a high solid content can be obtained. Atomization is a common method for preparing spherical powder. The traditional atomization method is a pyrolysis atomization method, which uses the high-frequency vibration of a circular piezoelectric ceramic piece in the thickness direction to break up the molecular bonds between liquid water molecules to produce water mist, and harmful gases such as nitrogen oxides are produced during pyrolysis atomization. Gas must be used as a carrier and then recovered. The equipment is complex and has many influencing factors (for example: atomization power, flow rate, temperature, carrier gas flow, etc.). The prepared spherical powder has low sphericity, low surface finish, large and uncontrollable particle size, wide particle size distribution and other problems, which makes it difficult to fully meet the requirements of actual applications. Summary of the Invention
[0006] The purpose of the present invention is to provide a silver-silicon dioxide spherical powder and a preparation method and application thereof.
[0007] The technical solution adopted by the present invention is:
[0008] A method for preparing silver-silicon dioxide spherical powder comprises the following steps:
[0009] 1) Dispersing silicon powder in sodium hydroxide solution by heating, and then adjusting the pH value of the dispersion to 2-4 to obtain acidic silica sol;
[0010] 2) mixing a silver nitrate solution and an acidic silica sol to prepare a solution to be atomized;
[0011] 3) bonding the microporous metal film to the polarized annular piezoelectric ceramic sheet to obtain an atomizing sheet;
[0012] 4) installing the atomizing plate into the ultrasonic atomizer, adding the solution to be atomized into the liquid storage tank of the ultrasonic atomizer, and then performing spray atomization and natural sedimentation to obtain a spherical gel;
[0013] 5) The spherical gel is subjected to heat treatment to obtain silver-silicon dioxide spherical powder.
[0014] Preferably, the mass fraction of the sodium hydroxide solution in step 1) is 4% to 10%.
[0015] Preferably, the heating dispersion in step 1) is carried out at 70°C to 90°C.
[0016] Preferably, the particle size of silicon dioxide in the acidic silica sol in step 1) is 8 nm to 20 nm, the concentration is 150 g / L to 480 g / L, and the mass fraction of Na2O is less than 0.1%.
[0017] Preferably, the viscosity of the acidic silica sol in step 1) is less than 10 mPa·s.
[0018] Preferably, the concentration of the silver nitrate in step 2) is 100 g / L to 2000 g / L.
[0019] Preferably, in step 2), the volume ratio of the silver nitrate solution to the acidic silica sol is 1:1-20.
[0020] Preferably, the microporous metal membrane in step 3) is a circular metal membrane having a plurality of tapered holes in the central region, a thickness of 0.05 mm to 0.1 mm, a circular arc-shaped protrusion in the central region, and a protrusion height of 0.1 mm to 0.3 mm. The tapered holes are arranged in an array in the same direction, the diameter of the large end of the tapered holes is 30 μm to 100 μm, the diameter of the small end is 3 μm to 10 μm, and the spacing between the tapered holes is 60 μm to 200 μm. The diameter of the small end of the tapered hole determines the diameter of the spray droplets.
[0021] Note: The "spacing between tapered holes" in the present invention refers to the distance between the centers of the tapered holes.
[0022] Preferably, in step 3), the microporous metal film is made by laser drilling.
[0023] Preferably, the thickness of the polarized annular piezoelectric ceramic piece in step 3) is 0.4 mm to 0.8 mm.
[0024] Preferably, in step 3), the microporous metal film and the polarized annular piezoelectric ceramic sheet are bonded by heat-curing epoxy adhesive.
[0025] Preferably, the spray atomization in step 4) is carried out under the conditions of an ultrasonic frequency of 100KHz to 180KHz and a peak-to-peak voltage of 40V to 90V on the atomizing plate.
[0026] Preferably, the natural sedimentation distance in step 4) is 40 cm to 100 cm.
[0027] Preferably, the heat treatment in step 5) is carried out at 500° C. to 800° C., and the heat treatment time is 1 hour to 6 hours.
[0028] A silver-silicon dioxide spherical powder is prepared by the above preparation method.
[0029] A conductive silver paste comprises the above-mentioned silver-silicon dioxide spherical powder.
[0030] A low-temperature co-fired ceramic, wherein the electrode composition includes the above-mentioned silver-silicon dioxide spherical powder.
[0031] The beneficial effects of the present invention are as follows: the silver-silicon dioxide spherical powder of the present invention has good sphericity, a smooth surface, adjustable conductivity, and a particle size that can be adjusted in a wide range; the preparation method is simple, the equipment requirements are low, and the production cost is low; the silver-silicon dioxide spherical powder fully meets the application requirements of conductive silver paste for LTCC and is suitable for large-scale application in the field of the electronics industry.
[0032] Specifically:
[0033] 1) The present invention adopts an ultrasonic microporous spray atomization method to prepare silver-silicon dioxide spherical powder. The microporous metal film adhered to the annular piezoelectric ceramic piece drives the microporous metal film to vibrate radially, and the tapered holes on the microporous metal film are used to spray out the solution to be atomized, which is made of silver nitrate solution and silica sol. The particle size distribution of the formed droplets is relatively narrow. The silica sol in the droplets will quickly evaporate in the air to form a gel and settle, thereby obtaining a small particle size and good sphericity (solidified in a suspended state in the air, the sphericity is higher, while the traditional pyrolysis atomization method has a small droplet volume during the atomization process. The spherical gel (which is easy to form tails and difficult to control sphericity) can be heat-treated to obtain a smooth surface (the droplets are gelled during the atomization process to obtain spheres with high surface finish, which can still maintain good surface finish after high-temperature treatment. Traditional pyrolysis atomization is to first pyrolyze into silver or silver oxide particles, and then sinter and fuse the particle agglomerates together at high temperature, so the surface finish is poor), silver-silicon dioxide spherical powder with adjustable conductivity and a wide range of adjustable particle size (the spherical powder particle size is adjusted by adjusting the diameter of the small end of the tapered hole on the microporous metal membrane);
[0034] 2) The present invention adopts an ultrasonic microporous jet atomization method to prepare silver-silicon dioxide spherical powder, which is easy to operate, has low equipment requirements, low production cost, does not require high-temperature treatment, is energy-saving and environmentally friendly, and is easy to achieve large-scale industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is an SEM image of the small end of the tapered hole on the microporous metal membrane in Example 1.
[0036] Figure 2 This is a particle size distribution diagram of droplets obtained by spray atomization in step 4) of Example 1.
[0037] Figure 3 This is an SEM image of the small end of the tapered hole on the microporous metal membrane in Example 2.
[0038] Figure 4 This is a particle size distribution diagram of droplets obtained by spray atomization in step 4) of Example 2.
[0039] Figure 5 The SEM image and EDS energy spectrum of the silver-silicon dioxide spherical powder in Example 3 are shown. DETAILED DESCRIPTION
[0040] The present invention will be further explained and illustrated below with reference to specific embodiments.
[0041] Example 1:
[0042] A silver-silicon dioxide spherical powder, the preparation method of which comprises the following steps:
[0043] 1) adding industrial silicon powder to a 10% by mass sodium hydroxide solution, heating to 70° C. and stirring to disperse the solution, then adding a hydrogenated cation exchange resin to adjust the pH of the dispersion to 4 to obtain an acidic silica sol (viscosity 8 mPa·s, wherein the silica particle size is approximately 8 nm, the concentration is 480 g / L, and the mass fraction of Na2O is 0.08%);
[0044] 2) Slowly adding a 2000 g / L silver nitrate solution to the stirred acidic silica sol at a constant speed, with the volume ratio of silver nitrate solution to acidic silica sol being 1:20, and stirring evenly to obtain a solution to be atomized;
[0045] 3) The central area of the metal film is laser-punched to form a microporous metal film, wherein the holes are conical holes, and the conical holes are arranged in an array in the same direction (the large ends of the conical holes are distributed on the same side of the microporous metal film, and the small ends are distributed on the other side). The microporous metal film is circular, with a diameter of 20 mm and a thickness of 0.1 mm. The central area has an arc-shaped protrusion, the diameter of the protrusion edge is 6 mm, and the protrusion height is 0.3 mm. The diameter of the large end of the conical hole is about 100 μm, and the diameter of the small end is about 10 μm. The number of conical holes is 400, and the spacing between the conical holes is about 200 μm. The microporous metal film is then bonded to the polarized annular piezoelectric ceramic piece with a thermosetting epoxy adhesive. The bonding is carried out at 160° C. and the holding time is 10 min. The outer diameter of the annular piezoelectric ceramic piece is 20 mm, the inner diameter is 10 mm, and the thickness is 0.8 mm, thereby obtaining an atomizing sheet.
[0046] 4) Installing the atomizing disc into an ultrasonic atomizer, adding the solution to be atomized into the ultrasonic atomizer's liquid reservoir, and then performing spray atomization under the conditions of an ultrasonic frequency of 100 kHz and a peak-to-peak voltage of 90 V on the atomizing disc, spraying the solution to be atomized into a closed space through the small end of the tapered hole on the microporous metal membrane, and allowing it to settle naturally over a settling distance of 100 cm to obtain a spherical gel;
[0047] 5) The spherical gel is placed at 800° C. for 1 h to obtain silver-silicon dioxide spherical powder.
[0048] The scanning electron microscope (SEM) image of the small end of the tapered hole on the microporous metal membrane in this embodiment is as follows: Figure 1 As shown, the particle size distribution of the droplets obtained by spray atomization in step 4) of this embodiment is as shown in FIG. Figure 2 shown.
[0049] Depend on Figure 2 It can be seen that the median particle size of the droplets (D 50 ) is about 10μm.
[0050] In addition, SEM and EDS tests show that the silver-silicon dioxide spherical powder of this embodiment has good sphericity and a smooth surface, a particle size of 1 μm to 8 μm, and a silver content of about 6 wt %.
[0051] Example 2:
[0052] A silver-silicon dioxide spherical powder, the preparation method of which comprises the following steps:
[0053] 1) adding industrial silicon powder to a 4% by mass sodium hydroxide solution, heating to 90° C. and stirring to disperse the solution, then adding a hydrogenated cation exchange resin to adjust the pH of the dispersion to 2 to obtain an acidic silica sol (viscosity 6 mPa·s, wherein the silica particle size is approximately 20 nm, the concentration is 150 g / L, and the mass fraction of Na2O is 0.06%);
[0054] 2) Slowly adding a 100 g / L silver nitrate solution to the stirred acidic silica sol at a constant speed, with the volume ratio of silver nitrate solution to acidic silica sol being 1:1, and stirring evenly to obtain a solution to be atomized;
[0055] 3) The central area of the metal film is laser punched to form a microporous metal film, the holes are conical holes, and the conical holes are arranged in an array in the same direction (the large end of the conical hole is distributed on the same side of the microporous metal film, and the small end is distributed on the other side). The microporous metal film is circular, with a diameter of 10 mm and a thickness of 0.05 mm. The central area has an arc-shaped protrusion, the diameter of the protrusion edge is 2 mm, and the protrusion height is 0.1 mm. The diameter of the large end of the conical hole is about 40 μm, the diameter of the small end is about 3 μm, the number of conical holes is 50, and the spacing between the conical holes is about 100 μm. The microporous metal film is then bonded to the polarized annular piezoelectric ceramic piece with a thermosetting epoxy adhesive. The bonding is carried out at 100° C. and the holding time is 60 min. The outer diameter of the annular piezoelectric ceramic piece is 10 mm, the inner diameter is 4 mm, and the thickness is 0.4 mm to obtain an atomizing sheet;
[0056] 4) Installing the atomizing disc into an ultrasonic atomizer, adding the solution to be atomized into the ultrasonic atomizer's liquid reservoir, and then spraying and atomizing the solution at an ultrasonic frequency of 180 kHz and a peak-to-peak voltage of 40 V on the atomizing disc. The atomized solution is sprayed into a closed space through the small end of the tapered hole on the microporous metal membrane and allowed to settle naturally over a settling distance of 40 cm to obtain a spherical gel;
[0057] 5) The spherical gel is placed at 500° C. for 6 h to obtain silver-silicon dioxide spherical powder.
[0058] The SEM image of the small end of the tapered hole on the microporous metal membrane in this embodiment is as follows: Figure 3As shown, the particle size distribution of the droplets obtained by spray atomization in step 4) of this embodiment is as shown in FIG. Figure 4 shown.
[0059] Depend on Figure 4 It can be seen that the D of the fog droplet 50 About 2.5μm.
[0060] In addition, SEM and EDS tests show that the silver-silicon dioxide spherical powder of this embodiment has good sphericity and a smooth surface, a particle size of 0.3 μm to 1.5 μm, and a silver content of about 18 wt %.
[0061] Example 3:
[0062] A silver-silicon dioxide spherical powder, the preparation method of which comprises the following steps:
[0063] 1) adding industrial silicon powder to a 6% by mass sodium hydroxide solution, heating to 80° C. and stirring to disperse the solution, then adding a hydrogenated cation exchange resin to adjust the pH of the dispersion to 3 to obtain an acidic silica sol (viscosity 4 mPa·s, wherein the silica particle size is approximately 10 nm, the concentration is 360 g / L, and the mass fraction of Na2O is 0.04%);
[0064] 2) Slowly adding a 1000 g / L silver nitrate solution to the stirred acidic silica sol at a constant speed, with the volume ratio of silver nitrate solution to acidic silica sol being 1:5, and stirring evenly to obtain a solution to be atomized;
[0065] 3) The central area of the metal film is laser-punched to form a microporous metal film, wherein the holes are conical holes, and the conical holes are arranged in an array in the same direction (the large ends of the conical holes are distributed on the same side of the microporous metal film, and the small ends are distributed on the other side). The microporous metal film is circular, with a diameter of 16 mm and a thickness of 0.05 mm. The central area has an arc-shaped protrusion, the diameter of the protrusion edge is 4 mm, and the protrusion height is 0.2 mm. The diameter of the large end of the conical hole is about 30 μm, and the diameter of the small end is about 3 μm. The number of conical holes is 3000, and the spacing between the conical holes is about 60 μm. The microporous metal film is then bonded to the polarized annular piezoelectric ceramic piece with a thermosetting epoxy adhesive. The bonding is carried out at 140° C. and the holding time is 30 min. The outer diameter of the annular piezoelectric ceramic piece is 16 mm, the inner diameter is 6 mm, and the thickness is 0.6 mm, thereby obtaining an atomizing sheet.
[0066] 4) Install the atomizing sheet into the ultrasonic atomizer, add the solution to be atomized into the liquid storage tank of the ultrasonic atomizer, and then spray atomize under the conditions of ultrasonic frequency of 140KHz and peak-to-peak voltage of 60V on the atomizing sheet (D 50The solution to be atomized is sprayed into a closed space through the small end of the tapered hole on the microporous metal membrane and allowed to settle naturally over a distance of 60 cm to obtain a spherical gel.
[0067] 5) The spherical gel is placed at 600° C. for 3 h to obtain silver-silicon dioxide spherical powder.
[0068] The SEM image and EDS spectrum of the silver-silicon dioxide spherical powder in this embodiment are as follows: Figure 5 (The small picture in the upper left corner is the EDS energy spectrum).
[0069] Depend on Figure 5 It can be seen that the silver-silicon dioxide spherical powder of this embodiment has good sphericity and a smooth surface, a particle size of 0.4 μm to 2 μm, and a silver content of about 15 wt%.
[0070] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be considered as equivalent replacement methods and are included in the scope of protection of the present invention.
Claims
1. A method for preparing silver-silicon dioxide spherical powder, characterized in that: The following steps are involved: 1) Heat the silicon powder and disperse it in a sodium hydroxide solution, and then adjust the pH value of the dispersion to 2-4 to obtain an acidic silica sol; 2) Mixing silver nitrate solution and acidic silica sol to prepare a solution to be atomized; 3) bonding the microporous metal film to the polarized annular piezoelectric ceramic sheet to obtain an atomizing sheet; 4) Installing the atomizing sheet into the ultrasonic atomizer, adding the solution to be atomized into the liquid storage tank of the ultrasonic atomizer, and then performing spray atomization and natural sedimentation to obtain a spherical gel; 5) heat-treating the spherical gel to obtain silver-silicon dioxide spherical powder; Step 3) The microporous metal membrane is a circular metal membrane with a plurality of conical holes in the central region, with a thickness of 0.05 mm to 0.1 mm, a circular arc-shaped protrusion in the central region, and a protrusion height of 0.1 mm to 0.3 mm. The conical holes are arranged in an array in the same direction, and the diameter of the large end of the conical hole is 30 μm to 100 μm, and the diameter of the small end is 3 μm to 10 μm, and the spacing between the conical holes is 60 μm to 200 μm; Step 4) the spray atomization is performed under the conditions of an ultrasonic frequency of 100KHz to 180KHz and a peak voltage of 40V to 90V on the atomizing sheet; Step 5) The heat treatment is carried out at 500°C to 800°C for 1 hour to 6 hours.
2. The preparation method according to claim 1, characterized in that: Step 1) The heating dispersion is carried out at 70°C to 90°C.
3. The preparation method according to claim 1 or 2, characterized in that: The particle size of silicon dioxide in the acidic silica sol of step 1) is 8nm-20nm, the concentration is 150g / L-480g / L, and the mass fraction of Na2O is less than 0.1%; the viscosity of the acidic silica sol of step 1) is less than 10mPa·s.
4. The preparation method according to claim 3, characterized in that: The concentration of the silver nitrate in step 2) is 100 g / L to 2000 g / L; the volume ratio of the silver nitrate solution to the acidic silica sol in step 2) is 1:1 to 20.
Citation Information
Patent Citations
Method for synthesis of silica loaded nickel-platinum catalyst by ultrasonic spray pyrolysis
CN103223347A
Method for preparing nano-scale catalyst through ultrasonic atomization plasma reaction
CN109590028A
Preparation method and device of silicon dioxide microspheres
CN109734102A
KR1018898280000B1